Reliability of Capillary Complete Blood Count in Children With Acute Gastroenteritis - Wielińska-Wiśniewska, Hanna; Nowak, Jan K.; Da̧browski, Michał; Szydłowska, Paula; Szczepanik, Mariusz; Cichocka, Katarzyna; Krzyżanowska-Jankowska, Patrycja; Walkowiak, Jarosław (Frontiers in Pediatrics, 2021)
Background: To assess the reliability of complete blood count (CBC) in the capillary blood of children with acute gastroenteritis (AGE), with a focus on leukocytes. Methods: This was a retrospective cross-sectional study. Complete blood count was compared between the capillary and venous blood in children admitted to a pediatric gastroenterology department with primary diagnosis of AGE (ICD-10 A09, A08.0, A08.2). Capillary blood was obtained in the emergency room and venous blood was sampled in the ward shortly thereafter during peripheral intravenous line placement. Results: One hundred forty children were included. The mean (±SD) age and weight of patients were 3.0±2.9 years and 16±9 kg; 26% had leukocytosis. The mean difference between obtaining results of capillary and venous blood tests was 2±1 hours. Area under the receiver operating characteristic curve (AUC) for the identification of leukocytosis using the capillary blood was 0.98 (95%CI 0.96–1.0). The sensitivity and specificity were 86% and 98%, respectively (accuracy 95%). The positive and negative predictive values were 94% and 95%, respectively. The intraclass correlation coefficient revealed high concordance between capillary and venous CBC measurements (leukocyte count 0.94, hemoglobin 0.88, erythrocyte count 0.77, hematocrit 0.79, platelet count 0.90). Matched pairs comparisons revealed marginally higher erythrocytes (difference of medians: 0.2 T/L), hemoglobin (0.3 g/dL), hematocrit (1.0%), and platelets (9 G/L) in the capillary blood. Conclusion: Capillary CBC is useful in detecting leukocytosis in children with AGE.